2019
DOI: 10.1113/jp277462
|View full text |Cite
|
Sign up to set email alerts
|

A hierarchy of corticospinal plasticity in human hand and forearm muscles

Abstract: Key points Pairing stimulation of a finger flexor or extensor muscle at the motor point with transcranial magnetic stimulation (TMS) of the motor cortex generated plastic changes in motor output. Increases in output were greater in intrinsic hand muscles than in the finger flexor. No changes occurred in the finger extensor. This gradient was seen irrespective of which muscle was stimulated paired with transcranial magnetic stimulation. Intermittent theta‐burst stimulation also produced increases in output, al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
15
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 47 publications
2
15
1
Order By: Relevance
“…These are promising results, but we recently showed that, in the upper limb, protocols which use sensory input to generate plasticity may have an intrinsic bias towards certain muscle groups. We showed that it was possible to generate robust changes generated in flexor and intrinsic hand muscles, but minimal effects in extensors (Foysal & Baker, 2019). Interestingly, this bias was not seen in a protocol which used only TMS, without paired sensory input.…”
Section: Introductionmentioning
confidence: 79%
“…These are promising results, but we recently showed that, in the upper limb, protocols which use sensory input to generate plasticity may have an intrinsic bias towards certain muscle groups. We showed that it was possible to generate robust changes generated in flexor and intrinsic hand muscles, but minimal effects in extensors (Foysal & Baker, 2019). Interestingly, this bias was not seen in a protocol which used only TMS, without paired sensory input.…”
Section: Introductionmentioning
confidence: 79%
“…In dystonia, the abnormality of sensory-motor plasticity might represent an endophenotypic trait that predisposes to the development of dystonia while in stroke patients it might be the structural brain lesion that results in a hand posture abnormality by interacting with an innate physiological asymmetry in the level of plasticity of cortical areas controlling different muscles. Of note is that the PAS protocol used by Riashad Foysal & Baker (2019), in which the motor point is stimulated instead of the peripheral nerve, seems not to have the same spatial specificity of the standard PAS described by Stefan et al (2000) in that stimulation of the motor point of either flexor digitorum superficialis or extensor digitorum communis induced plastic changes in both forearm flexors, and intrinsic hand muscles. The study by Riashad Foysal & Baker (2019) confirms that non-invasive brain stimulation techniques can provide unique insights into the physiological basis of human brain plasticity.…”
mentioning
confidence: 96%
“…Of note is that the PAS protocol used by Riashad Foysal & Baker (2019), in which the motor point is stimulated instead of the peripheral nerve, seems not to have the same spatial specificity of the standard PAS described by Stefan et al (2000) in that stimulation of the motor point of either flexor digitorum superficialis or extensor digitorum communis induced plastic changes in both forearm flexors, and intrinsic hand muscles. The study by Riashad Foysal & Baker (2019) confirms that non-invasive brain stimulation techniques can provide unique insights into the physiological basis of human brain plasticity. The assessment of sensory-motor plasticity in stroke might be useful for the early detection of changes that might interfere with functional recovery and also for the development and implementation of strategies aimed at Perspectives J Physiol 597.10 preventing the deleterious consequences of maladaptive plasticity.…”
mentioning
confidence: 96%
See 2 more Smart Citations